Convergence of Health Expenditure in OECD Countries: Evidence from a Nonlinear Asymmetric Heterogeneous Panel Unit Root Test - Pekkurnaz, Didem (Journal of Reviews on Global Economics, 2015)
This paper examines the convergence in health expenditure across 22 OECD countries between 1980 and 2012 by implementing panel unit root tests. Contribution of application of the nonlinear asymmetric heterogeneous panel unit root test is twofold. Firstly, it relaxes the assumption of cross-sectional dependency in panel data. Secondly, it incorporates the asymmetric nonlinear mean reversion in a panel setting. Results show that while the conventional panel unit root test cannot reject the null hypothesis of a unit root in relative per capita health expenditures for the whole set of countries, both the symmetric and the asymmetric nonlinear panel unit root tests indicate the stationarity of the panel. Specifically, almost 23 percent of the countries are found to be converging by employing the nonlinear asymmetric panel unit root test. In addition, introducing asymmetric structure helps to uncover additional converging countries which cannot be detected using linear and nonlinear symmetric panel unit root tests.